2021
DOI: 10.3389/fpsyg.2021.730341
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 on Parents of Pediatric Cancer Patients

Abstract: The changes and general alarm of the current COVID-19 pandemic have amplified the sense of precariousness and vulnerability for family members who, in addition to the emotional trauma of the cancer diagnosis, add the distress and fear of the risks associated with infection. The primary objectives of the present study were to investigate the psychological impact of the COVID-19 pandemic on the parents of pediatric cancer patients, and the level of stress, anxiety, and the child’s quality of life perceived by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 80 publications
2
28
1
Order By: Relevance
“…They also reported more mother-child time in a working day. These results are in line with the hypothesis and the literature available to date: chronically ill children's parents indicated greater concerns about contagion and worse psychological wellbeing when compared to healthy children's parents [14,15]; pediatric cancer patients' mothers reported clinical levels of anxiety during the pandemic [12]. Mothers must provide continuous assistance and might experience traumatic events completely on their own, also because the hospital allows only one parent to be present during the outpatients' visits and the hospitalizations as prevention measures.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…They also reported more mother-child time in a working day. These results are in line with the hypothesis and the literature available to date: chronically ill children's parents indicated greater concerns about contagion and worse psychological wellbeing when compared to healthy children's parents [14,15]; pediatric cancer patients' mothers reported clinical levels of anxiety during the pandemic [12]. Mothers must provide continuous assistance and might experience traumatic events completely on their own, also because the hospital allows only one parent to be present during the outpatients' visits and the hospitalizations as prevention measures.…”
Section: Discussionsupporting
confidence: 85%
“…This pattern is further aggravated by COVID-19, which works as a distressing experience [8,9]. Research on pediatric cancer patients during the COVID-19 pandemic revealed the risk of worse outcomes from infection because of immunosuppression [10], less treatment adherence [11], and parents' increased stress and anxiety [10,12]. Among the main psychological issues related to the COVID-19 pandemic in pediatric patients, particularly concerning are separation anxiety symptoms and COVID-19-related worries [13].…”
Section: Introductionmentioning
confidence: 99%
“…After the restrictions of COVID-19, considering the high psychopathological risk of the general population ( 82 ), we desired to pay attention to the physical and psychological impact of isolation and stress on cancer patients ( 83 – 85 ). Although the data are still few and partial, the oncology population, and their caregivers ( 86 ), are at risk of severe anxiety, stress, and depression ( 66 , 67 , 87 ) and long-term sequelae.…”
Section: Art Creativity and Technologies In Cancer Treatment: The Ita...mentioning
confidence: 99%
“…In addition to the uncertainty about the transmissibility of COVID‐19, worrying about treatment continuation was found to be more stressful for cancer patients and caregivers 1 . Caregivers experienced anxiety related to children contracting COVID‐19 and hospitals were no longer felt to be a safer place 2 . TheCOVID‐19 pandemic has caused greater impact on the mental health of paediatric patients, requiring professional mental health support 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Caregivers experienced anxiety related to children contracting COVID‐19 and hospitals were no longer felt to be a safer place. 2 TheCOVID‐19 pandemic has caused greater impact on the mental health of paediatric patients, requiring professional mental health support. 3 , 4 Although studies are being published around the pandemic situation in oncology with reference to psychosocial concerns, across different countries, there is scarce resources on psychosocial impact of COVID‐19 pandemic in low‐middle income countries, especially from India.…”
Section: Introductionmentioning
confidence: 99%